"y_1=(x-1)\\sqrt{(x+1)}\\\\\ny_2=-(x-1)\\sqrt{x+1}"
"y_1'=\\sqrt{(x+1)}+\\frac{(x-1)}{2\\sqrt{(x+1)}}=\\frac{3x+1}{2\\sqrt{(x+1)}}\\\\\ny_1''=\\frac{3}{2\\sqrt{(x+1)}}-\\frac{3x+1}{4(x+1)\\sqrt{(x+1)}}=\\\\\n\\frac{3x+5}{4(x+1)\\sqrt{(x+1)}}\\\\\ny_2'=-\\frac{3x+1}{2\\sqrt{(x+1)}}\\\\\ny_2''=-\\frac{3x+5}{4(x+1)\\sqrt{(x+1)}}"
zero of "y_1'=0\\ and \\ y_2'=0\\,is \\, x=-1\/3"
Since "y_1''(-1\/3)>0,\\ y_1" has minimum at this point.
Since "y_2''(-1\/3)<0,\\ y_2\\" has maximum at this point.
Since "0\\le y^2 \\ and \\ 0\\le(x-1)^2" ,it follows that "0\\le(x+1)\\ and\\ -1\\le x"
Intersections with axis:
"y=0, \\ (x+1)(x-1)\u00b2=0,\\ x=\\pm1"
"x=0,\\ y=\\pm 1"
Comments
Leave a comment